Perspectivas y desafíos en el desarrollo del pensamiento histórico desde la lectura crítica en educación básica y media (2017)
The objective of this research is to understand the dynamics of the use of critical reading in the development of historical thinking in students of the basic and secondary education levels. This exercise was focused on the implementation of action research from collective construction with two phases (diagnosis and transformation), taking as participants the teachers of social sciences or with academic assignment in this area in the Institución Educativa Departamental Rodrigo Vives de Andreis, in Orihueca town, Zona Bananera, department of Magdalena, Colombia. The instruments that were applied were discussion group, documentary review, classroom observation and training workshops, to verify transformation, a discussion group was applied. The results showed that in this institution the teachers had problems with the conceptual and procedural management of historical thinking and critical reading. In phase II the teachers, together with the researchers, during the process of training workshops achieved the construction of a lesson plan oriented to the development of historical thinking using critical reading, which allows them to reorient their pedagogical practice by join the elements required by the Ministry of National Education, in the construction of new didactics for the teaching process of history.